Atomic structure and electronic properties of the intercalated Pb atoms underneath a graphene layer. (July 2021) - Hu, Tingwei; Yang, Dong; Gao, Haitao; Li, Yan; Liu, Xiangtai; Xu, Kewei; Xia, Qianfeng; Ma, Fei
Abstract: Determining atomic structure of intercalated metallic layer under graphene is a hot-topic due to the potential applications in electronic engineering. In this study, Pb-intercalated graphene (PbG) is fabricated on SiC substrate and the atomic structure and electronic properties of the intercalated Pb atoms underneath graphene are investigated by scanning tunneling microscopy/spectroscopy (STM/STS). As the crystal facet of intercalated Pb atoms can be arranged in (111) (unit cell, 0.35 nm × 0.35 nm) and (110) (unit cell, 0.61 nm × 0.35 nm), mottled moiré pattern (period, 2.5 nm) and striated moiré pattern (period, 2.1 nm) are formed. Atomic arrangement of the intercalated Pb is sensitive to tip scanning resulting in the conversion of the two moiré patterns. Nevertheless, the crystal orientation of moiré patterns is always aligned with zigzag direction of graphene. As revealed by STS, PbG performs the similar electronic states to those of free-standing graphene due to the shielding effects of Pb intercalation. The crystallographic relationship between graphene and Pb atoms is also confirmed by density functional theory (DFT) calculations. The study provides crucial for understanding the structure of intercalated Pb atoms underneath a graphene layer, which may enable the development of new 2D materials capped by graphene. Graphical abstract: Image 1